2013
DOI: 10.1016/j.jcrs.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Posterior corneal elevation and back difference corneal elevation in diagnosing forme fruste keratoconus in the fellow eyes of unilateral keratoconus patients

Abstract: Back difference elevation was better than posterior elevation in diagnosing forme fruste keratoconus. However, as sole parameters, both had limited sensitivity and specificity to differentiate between forme fruste keratoconus eyes and normal control eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 20 publications
6
85
1
2
Order By: Relevance
“…The resulting “enhanced BFS” is supposed to approximate a normal cornea closely, making subtle elevations more pronounced and possibly aiding in detection of early or subclinical keratoconus. Various indices in normal eyes, keratoconus suspects, as well as established keratoconus have been measured, although definite superiority over earlier devices is yet to be proven 3843. Recent interest has focused on characterization of aberrometry profiles as well as understanding of corneal biomechanics in keratoconus using instruments such as the Ocular Response Analyzer (Reichert Inc, Depew, NY, USA).…”
Section: Imagingmentioning
confidence: 99%
“…The resulting “enhanced BFS” is supposed to approximate a normal cornea closely, making subtle elevations more pronounced and possibly aiding in detection of early or subclinical keratoconus. Various indices in normal eyes, keratoconus suspects, as well as established keratoconus have been measured, although definite superiority over earlier devices is yet to be proven 3843. Recent interest has focused on characterization of aberrometry profiles as well as understanding of corneal biomechanics in keratoconus using instruments such as the Ocular Response Analyzer (Reichert Inc, Depew, NY, USA).…”
Section: Imagingmentioning
confidence: 99%
“…1 Assessing the corneal curvature, corneal thickness, and corneal surface topography patterns and elevation readings are integral parts of a patient's workup. 2,3 Among various indices, keratometry has more applications in diagnosing and grading the disease, tracking disease progression, and planning treatment and patient follow-up. 2,4,5 Keratoconus patients usually have periodic examinations to determine the progression of the disease or the effect of treatment after surgery.…”
mentioning
confidence: 99%
“…For example, Muftuoglu et al 12 reported approximately 70% sensitivity for a range of different parameters between normal and fellow eyes of patients with keratoconus. However, the results of the current study were in agreement with those reported by Bae et al, 11 who found no difference in the BAD-D or ART-Max values between normal and topographically normal fellow eyes of patients with keratoconus.…”
Section: Discussionmentioning
confidence: 99%